Peningkatan Kompetensi Guru IPA melalui Pelatihan dan Pendampingan Pembuatan Perangkat dan Media Pembelajaran Berbasis Pendekatan Saintifik - Nurhayati Nurhayati; Dwi Fajar Saputri; Fety Novianty; Wahyudi Wahyudi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
This Community Partnership Program (PKM) aims to increase knowledge and train teachers to create and apply learning tools based on scientific approaches that contain the character and create and apply contextual and innovative media/props in learning. The method of implementing PKM activities consists of socialization, seminars, training, mentoring, and implementation. Participants in PKM activities are science teachers of SMP and equivalent who are members of the MGMP IPA of SMP Kota Singkawang. The results of the activity showed that (1) the teachers were enthusiastic about participating in the series of activities carried out, (2) the teachers were motivated to make science learning media and apply them in classroom learning, and (3) the teachers were motivated to create and apply models. a learning model based on a scientific approach that contains a character in classroom learning